EFEK KEPUASAN KERJA TERHADAP EMPLOYEE ENGAGEMENT DENGAN PSYCHOLOGICAL OWNERSHIP SEBAGAI MODERATOR - Setiabudhi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2016)
The purpose of the study is to investigate the influence of job satisfaction toward employee engagement through psychological ownership as the moderator. Research design used is a cross sectional study of 163 employees. Data is analyzed by multiple linear regression analysis. Result shows job satisfaction is able to influence employee engagement significantly through psychological ownership as the mediator. The p=0,000 with significance level 0,05. The sig F change shows 0,006, which is<0,05, therefore mederation effect is significant. Moderation effect also has a better influence than the direct effect. The effect is increasing from 27,2% without moderator to 31,5% with moderator.